How Rural China is Coping with COVID-19: Examining the Impacts on China's 600 Million Rural Residents ... 1, 2, 3 and 6 Months After! - Rozelle, Scott (2020)
Scott Rozelle POLICY SEMINAR Virtual Event - Evolving effects of COVID-19 on poverty and food security: What are we learning from China? JUL 28, 2020 - 09:30 AM TO 10:45 AM EDT